Column Preconcentration of Cobalt Using 4-(5-Bromo-2-pyridylazo)-1,3-diaminobenzene and Ammonium Tetraphenyl-broate Supported on Naphthalene and Its Analysis Using Atomic Absorption Spectrometry - Nagahiro, Tohru; Uesugi, Katsuya; Satake, Masatada (Asian Journal of Chemistry, 2010)
A method has been established for the determination of trace amount of cobalt employing column preconcentration of cobalt with 4-(5-bromo-2- pyridylazo)-1,3-diaminobenzene(5-Br-PADAB) and ammonium tetraphenylborate supported on microcrystalline naphthalene as an adsorbent for cobalt/5-Br-PADAB complex. The optimum pH range for the formation of cobalt/5-Br-PADAB complex and its adsorption on to the adsorbent packed into a column was 3.5–6.0. The column content was dissolved with N,N-dimethyl formamide and cobalt was determined using flame atomic absorption spectrometry. The calibration graph was linear up to 18 μg of cobalt in 5 ml of final solution. Seven replicate analyses for 12 μg of cobalt gave a mean absorbance of 0.110 with a relative standard deviation of 0.83%. The method has been applied for cobalt analysis in alloys, pepperbush and pond sediment.